Social Media as a Digital Communication Tool for Academic Library Marketing: A Systematic Literature Review - Wathsala Athukorala; Chaminda Chiran Jayasundara (Language, Technology, and Social Media, 2025)
This systematic literature review explores the role of social media as a digital communication tool in academic library marketing, synthesizing findings from 18 studies published between 2014 and 2024 across Web of Science, Scopus, and Emerald Premier. The analysis identifies key trends, strategies, challenges, and future directions, revealing that while social media is widely acknowledged for enhancing user engagement and institutional outreach, its implementation remains inconsistent. Challenges such as insufficient strategic planning, limited staff training, and low user engagement hinder effective utilization. The review underscores the importance of user-centred strategies, targeted communication, and linguistic adaptability including politeness strategies and register variation to optimize digital outreach. A proposed Social Media Marketing Engagement Model (SMMEM) offers a structured framework for libraries to align content with user needs, leverage analytics, and foster community interaction. Despite growing recognition of social media’s potential, gaps persist in evidence-based models and sociocultural considerations. Future research should prioritize developing metrics for evaluating engagement, comparative studies across diverse contexts, and training programs to enhance staff competency. By addressing these challenges, academic libraries can strengthen their digital presence, improve marketing efficacy, and adapt to evolving user expectations in the post-pandemic landscape.